Evaluation of a Training of Trainers Program on Food Safety and Nutrition Security - Mana-ay, Alvyn Klein A. (Philippine Social Science Journal, 2020)
Foodborne diseases (FBDs) remain a serious human health problem, and food safety plays an essential role in addressing this public health issue. This study aimed at evaluating the training of trainers program on food safety and nutrition security using a qualitative descriptive approach. The training exposed the participants to food safety topics in food processing and preservation with an emphasis on the nature of food safety hazards and the personal hygiene of food handlers in food preparation. The new trainers then organized and conducted actual seminar-workshops in their respective communities. The results of the evaluation indicate that the primary driver of the success of the program was institutional support by the local government partners. Overall, the program was able to achieve its ultimate goal of capacitating a group of local trainers on food safety in hopes of addressing the problem of FBDs through a cascade of training.